Quantum semiconductors based on Carbon materials for Nanophotonics, and Photonics applications by electron shuttle and near field phenomena - Bracamonte, Angel Guillermo (2023)
In This Review, it was it was intended to resume key Research reports and publications that open many themes and topics related with Carbon-based semiconductors and Quantum emitters. The Design and synthesis of high pure materials such as Graphene, Carbon Nanotubes, fullerenes as well other Carbon-based allotropes were showed and presented their most important and promising properties in relation with Photonics new studies and developments. Carbon-based Quantum dots, semiconductors, and higher sized Nanoplatforms permitted to discuss current fundamental studies and perspectives within varied applications. In this context, it was highlighted and discussed relevant development from literature related with Electron Transfer within varied targeted processes; where energy and light transfers occurred through different Optical active materials and platforms. Therefore, many approaches that lead to tune the desired Optical active properties were showed. Thus, Hybrid materials from single Quantum and Nanoplatforms towards modified substrates were incorporated within varied media such as colloidal dispersions and solid devices and waveguides. Moreover, Heterojunctions and applications such as energy harvesters, and emitter devices were presented as well. In this manner, varied topics of Photonics leading current status, perspectives and implications in Nanophotonics, Quantum photonics, and Optical lens were highlighted. Further perspectives and commentaries about Green Photonics were presented as well.